Wearable Biosensors in the Workplace: Perceptions and Perspectives - Tindale, Lauren C.; Chiu, Derek; Minielly, Nicole; Hrincu, Viorica; Talhouk, Aline; Illes, Judy (Frontiers in Digital Health, 2022)
Objectives: Wearable body and brain sensors are permeating the consumer market and are increasingly being considered for workplace applications with the goal of promoting safety, productivity, health, and wellness. However, the monitoring of physiologic signals in real-time prompts concerns about benefit and risk, ownership of such digital data, data transfer privacy, and the discovery and disclosure of signals of possible health significance. Here we explore the perceptions and perspectives of employers and employees about key ethical considerations regarding the potential use of sensors in the workplace. Methods: We distributed a survey developed and refined based on key research questions and past literature to a wide range and size of industries in British Columbia, Canada. Both employers (potential Implementers) and employees (potential Users) were invited to participate. Results: We received 344 survey responses. Most responses were from construction, healthcare, education, government, and utilities sectors. Across genders, industries, and workplace sizes, we found a convergence of opinions on perceived benefit and concern between potential Implementers and potential Users regarding the motivation to use biosensors in the workplace. Potential Implementers and Users also agreed on issues pertaining to safety, privacy, disclosure of findings of possible medical significance, risks, data ownership, data sharing, and transfer of data between workplaces. The greatest variability between potential Users and Implementers pertained to data ownership. Conclusion: Strong agreement in the perception of biosensor use in the workplace between potential Implementers and Users reflects shared interest, motivation, and responsibility for their use. The use of sensors is rapidly increasing, and transparency about key use factors – both practical and ethical – is essential to maintain the current and desirable level of solidarity.